Ghafar Baba kupasan oleh profesor dan cendekiawan Melayu - Alias Mohamed, 1945- (Gateway Pub. House, 1993)
Ghafar Baba, b. 1925, Malaysia's statesman and one of UMNO's political leaders; collection of articles.